Validity of Predictive Markers for Post ERCP Pancreatitis Patients: A Single Centre Study - Michael Tendean; Toar D. B. Mambu; Leonard A. Melatunan (Universitas Sam Ratulangi, 2024)
Abstract: Endoscopic retrograde cholangiopancreatography (ERCP) is a proprietary procedure, endoscopic modality, and specialized procedure used to diagnose and treat disorders of the pancreatic and biliary systems. The incidence of reported post-ERCP complications varied among several studies including post ERCP pancreatitis (PEP), duodenal perforation, and cholangitis. In this study, the author would like to show certain intra procedural factors related to PEP incidence. This was a retrospective study of secondary data of patients undergoing ERCP procedures from 2017-2022 at Prof. Dr. R. D. Kandou Hospital, Manado. Length of procedure, cannulation on pancreatic duct, pancreatogram, double wire technique, and the use of certain common bile duct (CBD) stone retrieval techniques such as endoscopic papillary balloon dilatation (EPBD) were recorded and analyzed. The results showed that based on the analyzed data, the percentage of pancreas cannulation was 8%, pancreatogram 5%, double-wire technique 3%, and EPBD procedure 10%, Incidence rate of PEP in all ERCP procedures was 19%. Increased amylase/lipase enzymes were found in 13 of 24 patients (54%) who underwent cannulation; 8 of 16 patients (50%) who underwent pancreatogram; 4 of 9 patients (44%) who underwent double wire procedure; and 10 of 30 patients (33%) who underwent EPBD. This PEP could be caused by several risk factors during ERCP including cannulation, pancreatogram, double wire, and EPBD. Number of cannulation attempt could result in trauma to the ampulla. Pancreatogram could result in hydrostatic, chemical, and allergic injury. Any manipulation of the pancreas that caused trauma could trigger the incidence of PEP. Assessment of the occurrence of PEP was based on increases in lipase and amylase enzyme values by four times the normal value and tested 6 hours after procedure. We could reduce the incidence of PEP by providing prophylactic therapy before ERCP. In conclusion, PEP is the most common complication in ERCP procedures and can be risky in patients with high risk factors. In this study, factors that affecting the incidence of PEP are cannulation, pancreatogram, double wire and EPBD. Keywords: endoscopic retrograde cholangiopancreatography; pancreatitis; complications